ALB–PRF facilitates chondrogenesis by promoting chondrocytes migration, proliferation and differentiation - Lijuan Zeng; Jun Zeng; Jianfeng He; Yang Zhou; Yongqi Li; Chengwei Li; Zhiyan Lin; Guangwei Chen; Huilin Wu; Libin Zhou (Platelets)
Cartilage injury is common in orthopedics and cartilage tissue engineering provides a therapeutic direction for cartilage regeneration. Albumin (ALB)–platelet-rich fibrin (PRF) is speculated to be an ideal natural scaffold material for cartilage tissue engineering theoretically as a product derived from human venous blood. Through in vitro and in vivo experiments, it was demonstrated that ALB–PRF displayed porous structure and slowly released growth factors (TGF-β1, PDGF-AA, PDGF-AB, PDGF-BB, EGF, IGF-1 and VEGF), ALB–PRF conditioned media promoted proliferation, migration, adhesion, phenotype maintenance and extracellular matrix secretion of rabbit chondrocytes. Moreover, ALB–PRF facilitated chondrogenesis in vivo, the regenerative cartilage formed by ALB–PRF/chondrocytes was histologically similar to that of natural knee joint cartilage, the regenerative cartilage expressed cartilage differentiation marker (SOX9, ACAN and COL II), and proliferation marker PCNA and secreted abundant glycosaminoglycans (GAGs) in extracellular matrix. In conclusion, ALB–PRF promoted the migration, proliferation and phenotype maintenance of chondrocytes in vitro. Its loose, porous structure and rich growth factors contained enhanced cell adhesion and growing into the materials. ALB–PRF facilitated chondrogenesis of chondrocytes in vivo.